2010
DOI: 10.2340/16501977-0468
|View full text |Cite
|
Sign up to set email alerts
|

The International Classification of Functioning Disability and Health, version for children and youth as a roadmap for projecting and programming rehabilitation in a neuropaediatric hospital unit

Abstract: ICF-CY may work as a road-map for in-hospital paediatric neuro-rehabilitation. Its implementation results in perceived improvements in the process. Training requirements and accurate evaluation of timing, workload and organizational context are critical issues that should be addressed before results from the present experience are generalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…In particular, the ICF-CY based project/program format that we used in this case [18], gave a global description of the person's functioning, highlights the specific rehabilitation objectives and allows verification of any changes brought about by the DBS treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the ICF-CY based project/program format that we used in this case [18], gave a global description of the person's functioning, highlights the specific rehabilitation objectives and allows verification of any changes brought about by the DBS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a dystonic child treated with DBS was described using the ICF-CY perspective [10,18]. This model guides the rehabilitation team to first break up the patient's clinical picture in little and different pieces (specific domains and categories) and then, to recompose the full picture as a puzzle with its pieces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This claim holds up well based on the first wave of research. Exploring the utility of the ICF-CY across various combinations of public health, local health agencies, social services, multidisciplinary hospital teams, regional educational systems, and health service researchers, ICF-CY research endorses its contribution to framing the understanding of functional characteristics of children with specific diagnoses over time and to plan and coordinate intervention plans within and across sectors (Bonanni et al, 2009;De Polo, Pradal, Bortolot, Buffoni, & Martinuzzi, 2009;Fusaro, Maspoli, & Vellar, 2009;Martinuzzi et al, 2010;Salghetti et al, 2009). One multidisciplinary health team reported that the ICF-CY created an "opportunity for a stronger convergence on targets and goals, a better concordance with children's families on the general project, and .…”
Section: Clarifying Cross-disciplinary Communicationmentioning
confidence: 99%
“…Reabilitacijos specialistai, kurių kasdienė darbo praktika susijusi su funkcionavimo vertinimu, kritikuoja klasifikaciją kaip gremėz-dišką ir dėl to sunkiai taikomą praktiniame darbe Didelis kategorijų skaičius taip pat riboja praktinį klasifikacijos taikymą [19]. Kai kurie mokslininkai aprašo klasifikacija grįstų vertinimo priemonių su protingu kategorijų skaičiumi trūkumą [5].…”
Section: Tfk-vj Skyriaiunclassified